Visual fatigue and visual evoked potentials in multiple sclerosis, glaucoma, ocular hypertension and Parkinson's disease. - Regan, D (1984)
Visual evoked potential (VEP) abnormality is widely used as an objective indication of visual pathophysiology in the diagnosis of multiple sclerosis. One major limitation of this test is that VEP abnormality is not specific to multiple sclerosis. In an attempt to explore ways of making the VEP test more specific, changes were measured in VEPs caused by superimposing upon the VEP stimulus either a flicker or a moving pattern. The rationale was to test for visual fatigueability, since it is known that some demyelinated axons fatigue rapidly. Of 10 patients with multiple sclerosis, 90% showed VEP fatigue, while none fatigued in the groups of 10 patients with glaucoma and 10 with Parkinson's disease. Fatigue is, however, not completely specific for multiple sclerosis, since three of 10 patients with ocular hypertension showed VEP fatigue.